Regulation of Coronary Blood Flow by the Carotid Body Chemoreceptors in Ovine Heart Failure - Pachen, Mridula; Abukar, Yonis; Shanks, Julia; Lever, Nigel; Ramchandra, Rohit (Frontiers in Physiology, 2021)
Carotid bodies (CBs) are peripheral chemoreceptors, which are primary sensors of systemic hypoxia and their activation produces respiratory, autonomic, and cardiovascular adjustments critical for body homeostasis. We have previously shown that carotid chemoreceptor stimulation increases directly recorded cardiac sympathetic nerve activity (cardiac SNA) which increases coronary blood flow (CoBF) in conscious normal sheep. Previous studies have shown that chemoreflex sensitivity is augmented in heart failure (HF). We hypothesized that carotid chemoreceptor stimulation would increase CoBF to a greater extent in HF than control sheep. Experiments were conducted in conscious HF sheep and control sheep (n=6/group) implanted with electrodes to record diaphragmatic electromyography (dEMG), flow probes to record CoBF as well as arterial pressure. There was a significant increase in mean arterial pressure (MAP), CoBF and coronary vascular conductance (CVC) in response to potassium cyanide (KCN) in both groups of sheep. To eliminate the effects of metabolic vasodilation, the KCN was repeated while the heart was paced at a constant level. In this paradigm, the increase in CoBF and CVC was augmented in the HF group compared to the control group. Pre-treatment with propranolol did not alter the CoBF or the CVC increase in the HF group indicating this was not mediated by an increase in cardiac sympathetic drive. The pressor response to CB activation was abolished by pre-treatment with intravenous atropine in both groups, but there was no change in the CoBF and vascular conductance responses. Our data suggest that in an ovine model of HF, carotid body (CB) mediated increases in CoBF and CVC are augmented compared to control animals. This increase in CoBF is mediated by an increase in cardiac SNA in the control group but not the HF group.